Proceedings of SPE Annual Technical Conference and Exhibition 1995
DOI: 10.2523/30783-ms
|View full text |Cite
|
Sign up to set email alerts
|

Waterflood Recovery and Fluid Flow Upscaling in a Shallow Marine and Fluvial Sandstone Sequence

Abstract: Detailed reservoir characterisation and modelling has been an active area of petroleum technology development for several years now, but incorporating and scaling up these geologic models into fluid flow and production simulations is a major challenge. The objective of this study is to properly incorporate all relevant levels geological heterogeneity identified in a detailed outcrop reservoir description into a flow simulation of an hypothetical reservoir. We apply the "geopseudo" upscaling methodology to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, these pictorial records are difficult or impossible to incorporate into the gridded data structures required for reservoir simulation. Modeling of fluid flow through heterogeneous hydrocarbon reservoirs and aquifers requires a more structured integration of stratal geometry and rock property observations, and a greater emphasis on unambiguous quantitative prediction of petrophysical variations throughout the deposit (e.g., Anderson 1989;Dreyer et al 1993;Ciametti et al 1995;Koltermann and Gorelick 1996;White and Barton 1999). Some types and scales of geologic variation may have little influence on fluid flow, whereas other variations may be critical to accurate prediction.…”
Section: Introductionmentioning
confidence: 99%
“…However, these pictorial records are difficult or impossible to incorporate into the gridded data structures required for reservoir simulation. Modeling of fluid flow through heterogeneous hydrocarbon reservoirs and aquifers requires a more structured integration of stratal geometry and rock property observations, and a greater emphasis on unambiguous quantitative prediction of petrophysical variations throughout the deposit (e.g., Anderson 1989;Dreyer et al 1993;Ciametti et al 1995;Koltermann and Gorelick 1996;White and Barton 1999). Some types and scales of geologic variation may have little influence on fluid flow, whereas other variations may be critical to accurate prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Their effect on two-phase fluid flow is less well understood. Other studies 10,11 have suggested that oil located in the junction where two shales intersect is bypassed by the displacing fluid; in this case, the oil remains trapped by the shales (fig. 1b).…”
Section: Introductionmentioning
confidence: 87%
“…They computed the effective properties for the geological units at the geostatistical scale by up-scaling from a small-scale description, and the properties at the simulation scale from a second up-scaling using the effective properties from the first step as input. Similar approaches were used earlier by Ciammetti et al 15 and Stephen et al 16 in which the effect of very small-scale heterogeneities was included in the generation of the pseudo-functions for various geological facies. A review of application of the pseudo-relative permeabilities for up-scaling is given by Barker and Thibeau 17 Barker and Dupouy 18 present a comparison among five different methods of dynamic pseudo-relative permeabilities.…”
Section: Introductionmentioning
confidence: 98%
“…The densities o ρ and w ρ are evaluated under the standard conditions. We then combine Eqs (15). and(16)to obtain a single equation for P o which contains no explicit time derivatives of the phase saturations:…”
mentioning
confidence: 99%